ANALISIS EFISIENSI TENAGA KERJA USAHATANI PADI ( Oryza sativa L ) PADA LAHAN KERING DENGAN CARA TANAM JAJAR LEGOWO DI DESA SUNGAI LURUS - Yayuk Minta Wahyuningsih; Muhamad Baparki (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
This research was conducted to know, level of labor efficiency of rice farm effort. A survey with an observation technique was used as a method, where farmers follow the example of taken at random modestly as much as 29 farmers. Result of research obtained by the story, level of productivity equal to 2.081,44 kg/ha, and acceptance equal to Rp 16.651.538,46 /ha. Distribution of external labour family( TKLK) 88,73 % and family labour ( TKDK) 11,27 % from totalizing the labour effusing. while the allocation for labor cost equals to75,85 % to total cost representing a group of biggest expense rice. Count efficiency of labor from the facet of labor productivity obtained value17,18 kg/HKO, from facet labor Productivity Index Obtained Rp 84.046,71 /HKO and from wide facet equal to 82,54 m2/HKO.